Compensation Management System at the Tanjungpinang Class II Port Authority and Municipal Office - Arib Darlicza; Silvia Fitriani; Satriadi Satriadi (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study aims to describe the employee compensation management system implemented in the Tanjungpinang Class II Port Authority and Municipal Office (KSOP). This study uses a descriptive method with a qualitative approach. Data collection was carried out by interview and direct observation techniques. The sample used in this study is purposive sampling. The informant in this study is Mr. Harry Priambodo, S.Pi. as the head of the administrative sub-division at the Tanjungpinang Class II Port Authority and Municipal Office (KSOP). The data analysis used in this study was carried out through three stages, namely data reduction, presenting data, and making conclusions. The results of the study show that the implementation of the employee compensation management system at the Tanjungpinang Class II Municipal and Port Authority Office has been running in accordance with applicable regulations and has a positive impact on employee performance. This can be seen from the regularity in the management of basic salaries, allowances, and work facilities such as BPJS Kesehatan, BPJS Employment, and supporting equipment. The procedure begins with performance measurement based on discipline and work achievement monitored through digital and manual attendance. The system also supports career development through Periodic Raises and promotions.